Analysis of The Use of Super Book Media on the Development of Language and Fine Motor Skills in Early Childhood - Udju, Anita A. Hege; Jaga, Maria Regina; F. Tamelab, Maryance; Eki, Vitha (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to evaluate the impact of using Super Book video media in early childhood learning. The method used in this research is Classroom Action Research. Focus on language and fine motor development of children aged 4-5 years through super book Videos. Before intervention, the majority of children did not show significant progress. However, the results of Cycle 1 showed positive changes, with a decrease in children who were not yet developing to 40%, an increase in children who were beginning to develop to 35%, and children who were developing very well increased to 20%. Cycle 2 noted increased focus, active participation, and storytelling ability. These results confirm the effectiveness of the Video Super book in improving children's language and fine motor development. Media preparation, the role of parents, and support from early childhood education managers are important factors. This recommendation is expected to strengthen the contribution of SuperBook media to early childhood development.